2022
DOI: 10.1016/j.jamda.2021.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Risk Factors for Extended-Spectrum β-Lactamase–Producing Enterobacterales in Long-Term Care Residents

Abstract: Objectives: We aimed to assess the burden of extended-spectrum b-lactamase (ESBL)-producing Enterobacterales in Swiss long-term care facilities (LTCFs) to describe the molecular epidemiology, describe the intrainstitutional and regional clusters of resistant pathogens, and identify independent institution-and resident-level factors associated with colonization. Design: Cross-sectional study. Setting and Participants: From August to October 2019, we performed a point prevalence study among residents from 16 LTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…For instance, in Switzerland (2010–2020), 10.5% of the long-term care facilities (LTCF) residents were colonized with ESBL- Ec , of which 58% belonged to the pandemic sequence type (ST) 131 lineage [ 73 ]. Consistent results were obtained in a more recent national Swiss study (2019), with an ESBL- Ent carriage of 11.6% and again a high prevalence of ST131 Ec strains [ 74 ]. In an Italian study (2008), 64% of the LTCF residents were colonized with ESBL- Ent , while 6.3% had CPE.…”
Section: Epidemiology and Risk Factorssupporting
confidence: 85%
“…For instance, in Switzerland (2010–2020), 10.5% of the long-term care facilities (LTCF) residents were colonized with ESBL- Ec , of which 58% belonged to the pandemic sequence type (ST) 131 lineage [ 73 ]. Consistent results were obtained in a more recent national Swiss study (2019), with an ESBL- Ent carriage of 11.6% and again a high prevalence of ST131 Ec strains [ 74 ]. In an Italian study (2008), 64% of the LTCF residents were colonized with ESBL- Ent , while 6.3% had CPE.…”
Section: Epidemiology and Risk Factorssupporting
confidence: 85%
“…As antibiotic use has been found as a risk factor for resistance in many other studies, 14,15,22 we cannot rule out that antibiotic use plays a role in ESBL-E carriage. There are reports identifying an association between the use of gastric acid suppressive medication and intestinal colonization or infections with ESBL-E. 18,21,23,33,34,46…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for ESBL-E gastrointestinal carriage have been described. However, these have, with a few exceptions 13,14 , mainly been investigated in small and/or selected study populations, such as international travelers 15 , patients with gastroenteritis 16 , patients recruited by general practitioners 17 , persons with recent healthcare contact 18 , pregnant women 19 , children 20 or persons living in a livestock-dense area 21 . Many studies have identified international travel as a risk factor for ESBL acquisition, whilst the significance of sex, age, antibiotic or proton pump inhibitor use, hospitalization and diet are conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations